Kebijakan Editorial Surat Kabar Harian Medan Bisnis dalam Pemberritaan Masalah Ekonomi dan Bisnis - Nurhalim Tanjung (Persepsi: Communication Journal, 2018)
This study attempts to reveal the editorial policy of MedanBisnis Daily newspaper in reporting economic and business issues using agenda theory of media settings and influence hierarchies. The method in this study uses a descriptive qualitative approach. The study was conducted in the period March-December 2014.The results of this study indicate the Medan Daily Business is a local economic newspaper that prioritizes reporting on the economic sector and micro-scale business. But the macro and national and international economic news is also a concern for this newspaper if it impacts on the local community in North Sumatra. In addition, the five levels as a factor of "hierarchy of influence" influenced the MedanBisnis Daily editorial policy in reporting economic and business issues